Continuous Clean Water Flow Technique in Washing Machine - Mohd Hudzari, Haji Razali; Soran Jalal, Abdullah; Syazili, Roslan; Basri, Ibrahim; Mohd Shahril, Othman; Noordin Asimi, Mohd Noor (2015)
Many people are not exposed in the proper way to wash clothes mixed with dirt, or clothes spattered Hukmi stool (dirt are not visible and surely exposed to unclean), it should be repeated on washing through a rinse with continous flow of clean water . The water that occupied in the washing machine is less than two tanks (216 litres) and if having stool clothes inside washing drum will caused Mutannajis and the water cannot be used for cleaning purpose. Then the Syariahlaw ofprayers like Solahis not valid because the clothes still bear dropped unclean. Before washing machine created, Muslims wash their clothes in the river, or water from pipes or water jars, the water is flowing and is not bound by problem arise. With the same concept, the electronic controller command of Programmable Logic Controller (PLC) will be added onexisting washing machine system so that the continous flowing of clean water will be channeledduring Spin mode duration. Omron optic sensors have been used to determine the stage of Spin mode in washing machine and will thentriggering the signal through PLC microcontroller to act opening of solenoid valve for assessing the clean water flow inside washing machine’s drum. Practically clean water will flow into rotating drum that having clothes and then will move out through water outlet valve of washing machine. The water flow is expected to flow continously in 10 minutes with volume of approximetly 10 litres and the Spin mode process will then continous in another 10 minutes for drying purpose. This novelty is not to deny the existing washing machine in the market but here is to introduce the best practise for complying Islamic Shariahon the flowing water technique in nowdays washing machine.